Analisis dan Penilaian Bisnis Perusahaan BUMN di Industri Farmasi: Studi Kasus Kimia Farma dan Indofarma Tahun 2006-2008 - Lovinta Valentina Handayani; Mohamad Heykal (Bina Nusantara University, 2012)
The objective of this research were R to determine the financial ratios as a basis to describe the financial performance and compare stock prices to book value (PBV) and evaluate the rate of return between the two companies by using the Du Pont analysis, with the focus for pharmaceutical industries in Indonesia. The benefit to provide an overview of financial performance of both companies. Then predicted to prospective investors on the cheap or expensive a stock. Provide recommendations to potential investors to make investment decisions. The method used is the ratio method and the percentage sales method. The conclusion can be that the performance of Finance at PT Kimia Farma as part of Indonesian pharmaceutical industries largely increased from year to year, while PT Indofarma largely decreased. PT Indofarma stock price is cheaper than PT Kimia Farma. The rate of return is relatively stable PT Kimia Farma and PT Indofarma has decreased from year to year. For the moderate investor PT Kimia Farma is the right choice.